Iodine Excretion in 24-hour Urine Collection and Its Dietary Determinants in Healthy Japanese Adults - Ryoko Katagiri (Journal of Epidemiology, 2016)
Background: Since seaweed is a common component of the Japanese diet, iodine intake in Japanese is expected to be high. However, urinary iodine excretion, measured using 24-hour urine samples, and its dietary determinants are not known. Methods: Apparently healthy adults aged 20 to 69 years living in 20 areas throughout Japan were recruited in February and March, 2013. Urinary iodine excretion was evaluated using 24-hour urine collected from 713 subjects (362 men and 351 women), and the difference among age groups was assessed. The association between dietary intake of food groups and urinary iodine excretion was assessed among 358 subjects who completed a semi-weighed 4-day diet record (DR) and urine collection. The correlations between iodine intake and iodine excretion were also evaluated, and correlation coefficients were calculated for iodine intake in the DR of the overlapping day or the DR 1 day before and after urine collection. Results: Median iodine excretion in 24-hour urine was 365 µg, and excretion was significantly higher in older subjects. Iodine intake estimated by the DRs was significantly correlated with urinary iodine excretion when DRs and urine collection were obtained on the same day (r = 0.37). After adjustment for confounding factors, iodine excretion was significantly associated with intakes of kelp and soup stock from kelp and fish. Conclusions: Although multiple measurements for urinary iodine are required to confirm our results, this study showed the current iodine status of healthy Japanese adults. The results suggest that kelp and fish are the main contributors to Japanese iodine status measured by 24-hour urine.